Teknik SCAMPER : Stimulasi Kreativitas Mahasiswa Calon Guru Biologi pada Aktivitas Laboratorium - Listika Yusi Risnani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This study aims to improve the creativity of pre service biology teacher in laboratory activities. This research type is pre-experiment with population as many as 34 student of semester 1 at Biology Education Study Program of Muhammadiyah University of Purwokerto. The study was conducted in the sixth semester of the 2017/2018 academic year as much as six treatments in the biology practicum course. Instrument of data collection in the form of observation sheet, document, non objective description test instrument. Data were analyzed by using quantitative and qualitative descriptive technique. The results showed that treatment using SCAMPER technique successfully stimulated student creativity with average value of 88,50 (very good) in experimental or experiment design activity, creativity of basic skills with average value of 52 (less), process skills with average values of 71 (good), and investigative skills with an average value of 62 (enough). The conclusion of this research is that SCAMPER technique is effective to stimulate student creativity in designing experiment / practice, process skills, and investigative skills, but still not effective to improve creativity of basic skills in laboratory activities.